PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW MATERI SISTEM EKSKRESI UNTUK MENINGKATKAN HASIL BELAJAR MURID SMP - Febri Nurdian Afifah; Erman Erman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to determine improvements in junior high school students’ science learning outcomes, the implementation of instruction, and student responses following the application of the Jigsaw cooperative learning model to the topic of the excretory system. The research design employed was a pre-experimental design using a one-group pretest-posttest design. The subjects of this study were the 32 students in Class VIII-A at Bahrul Ulum Junior High School in Surabaya. The cognitive learning outcome indicators used include understanding, applying, and analyzing. The results of the study indicate that there is a significant difference between pretest and posttest scores after the implementation of the Jigsaw cooperative learning model, with a Wilcoxon test significance value of 0.000 < 0.05. The N-Gain analysis results show an improvement in student learning outcomes of 0.5718, categorized as moderate. The implementation of the learning process was rated as very good, with a mode score of 4 for the introductory, main, and concluding activities. Additionally, student responses to the learning process were rated as very good, with an average percentage of 91%, indicating that students felt engaged, active, and supported in understanding the excretory system material through the implemented learning approach. Based on these results, it can be concluded that the Jigsaw cooperative learning model is effective in improving junior high school students’ science learning outcomes. ABSTRAK Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPA murid SMP, keterlaksanaan pembelajaran, serta respons murid setelah diterapkan model pembelajaran kooperatif tipe Jigsaw pada materi sistem ekskresi. Jenis penelitian yang digunakan adalah pre-experimental design dengan rancangan One Group Pretest Posttest. Subjek dalam penelitian ini adalah murid kelas VIII-A SMP Bahrul Ulum Surabaya dengan jumlah 32 murid. Indikator hasil belajar kognitif yang digunakan meliputi memahami, menerapkan, dan menganalisis. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara nilai pretest dan posttest setelah diterapkan model pembelajaran kooperatif tipe Jigsaw, dengan nilai signifikansi uji Wilcoxon sebesar 0,000 < 0,05. Hasil analisis N-Gain menunjukkan peningkatan hasil belajar murid sebesar 0,5718 dengan kategori sedang. Keterlaksanaan pembelajaran berada pada kategori sangat baik dengan skor modus 4 pada kegiatan pendahuluan, inti, dan penutup. Selain itu, respons murid terhadap pembelajaran menunjukkan kategori sangat baik dengan rata-rata persentase sebesar 91%, yang menandakan bahwa murid merasa tertarik, aktif, dan terbantu dalam memahami materi sistem ekskresi melalui pembelajaran yang diterapkan. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model pembelajaran kooperatif tipe Jigsaw efektif untuk meningkatkan hasil belajar IPA murid SMP.